2022
DOI: 10.3389/fcvm.2022.897087
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Glycocalyx: A Possible Therapeutic Target in Cardiovascular Disorders

Abstract: The physiological, anti-inflammatory, and anti-coagulant properties of endothelial cells (ECs) rely on a complex carbohydrate-rich layer covering the luminal surface of ECs, called the glycocalyx. In a range of cardiovascular disorders, glycocalyx shedding causes endothelial dysfunction and inflammation, underscoring the importance of glycocalyx preservation to avoid disease initiation and progression. In this review we discuss the physiological functions of the glycocalyx with particular focus on how loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 203 publications
0
29
0
Order By: Relevance
“…Diverse factors, including disturbed or reduced flow profiles, vascular aging, diabetes, and obesity, determine biochemical and structural alterations in EG associated with the onset of endothelium dysfunction [ 108 , 109 , 110 , 111 ]. In addition, recent evidence has shown that EG is considered as one of pathological conditions commonly accompanying an ischemia/reperfusion injury (IRI), along with tissue damage due to ROS produced upon reperfusion, mitochondrial dysfunction with opening of the mitochondrial transition pore and loss of ATP production, activation of the complement system, and endothelial dysfunction [ 112 , 113 ]. Animal models of cardiac IRI have demonstrated an early reduction in the thickness of EG, precisely 5 min after reperfusion, whereby EG shedding causes a reduced vasodilation of the endothelium mediated by NO.…”
Section: Vascular Endothelial Glycocalyx and Its Components As Emergi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse factors, including disturbed or reduced flow profiles, vascular aging, diabetes, and obesity, determine biochemical and structural alterations in EG associated with the onset of endothelium dysfunction [ 108 , 109 , 110 , 111 ]. In addition, recent evidence has shown that EG is considered as one of pathological conditions commonly accompanying an ischemia/reperfusion injury (IRI), along with tissue damage due to ROS produced upon reperfusion, mitochondrial dysfunction with opening of the mitochondrial transition pore and loss of ATP production, activation of the complement system, and endothelial dysfunction [ 112 , 113 ]. Animal models of cardiac IRI have demonstrated an early reduction in the thickness of EG, precisely 5 min after reperfusion, whereby EG shedding causes a reduced vasodilation of the endothelium mediated by NO.…”
Section: Vascular Endothelial Glycocalyx and Its Components As Emergi...mentioning
confidence: 99%
“…However, the mechanism underlying EG restoration. and whether its physiological composition is maintained, has not yet been explored [ 113 ]. However, various preventive and restorative approaches, with the aim of recreating physiological EG functions, have been proposed as potential therapies for endothelial dysfunction and its complications.…”
Section: Vascular Endothelial Glycocalyx and Its Components As Emergi...mentioning
confidence: 99%
“…Diverse factors, including disturbed or reduced flow profiles, vascular aging, diabetes, and obesity determine biochemical and structural alterations in EG associated with the onset of endothelium dysfunction [108][109][110][111]. In addition, recent evidence has shown that EG is considered as one of pathological conditions commonly accompanying an ischemia/reperfusion injury (IRI), along with tissue damage due to ROS produced upon reperfusion, mitochondrial dysfunction with opening of the mitochondrial transition pore and loss of ATP production, activation of the complement system, and endothelial dysfunction [112,113]. ).…”
Section: Vascular Endothelial Glycocalyx and Its Components As Emergi...mentioning
confidence: 99%
“…In addition, it was demonstrated that the EG can regenerate over time; specifically, some in vivo studies have revealed that about 7 days are sufficient to reestablish the EG layer. However, the mechanism underlying EG restoration and whether or not its physiological composition is maintained has not yet been explored [113]. However, various preventive and restorative approaches, with the aim of recreating physiological EG functions, have been proposed as potential therapies for endothelial dysfunction and its complications.…”
Section: Vascular Endothelial Glycocalyx and Its Components As Emergi...mentioning
confidence: 99%
“…Following the proliferation of endothelial cells, the composition of the eGCX layer is important for the formation of normal vascular morphology and functions in the process of tube formation ( 114 , 134 , 135 ). Synthesis of the eGCX is initiated by the enzyme EXTL1-3 with the side chain elongation mediated by EXT1-2 ( 136 ). It has been proposed that there is a dynamic equilibrium between the shedding of eGCX components under pathologic conditions, the adsorption of the components from circulating blood, and synthesis of eGCX, which indicates a tendency to maintain an intact eGCX layer within afflicted vessels ( 137 , 138 ).…”
Section: Potential Mechanisms Linking Egcx To the Pathogenesis Of Hpsmentioning
confidence: 99%